2018
DOI: 10.1111/tpj.14019
|View full text |Cite
|
Sign up to set email alerts
|

MCRiceRepGP: a framework for the identification of genes associated with sexual reproduction in rice

Abstract: Rice is an important cereal crop, being a staple food for over half of the world's population, and sexual reproduction resulting in grain formation underpins global food security. However, despite considerable research efforts, many of the genes, especially long intergenic non-coding RNA (lincRNA) genes, involved in sexual reproduction in rice remain uncharacterized. With an increasing number of public resources becoming available, information from different sources can be combined to perform gene functional a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 64 publications
0
18
0
Order By: Relevance
“…Improving our understanding of the functions and interactions between the core and variable genes will significantly add value to pan-genome studies. One possible approach involves integrative genomics methodologies, which aim to link properties of genes such as expression level, connectivity in biological networks, and sequence conservation to their function 76,77 to gain a broader understanding of their potential function.…”
Section: Prospects and Future Directionsmentioning
confidence: 99%
“…Improving our understanding of the functions and interactions between the core and variable genes will significantly add value to pan-genome studies. One possible approach involves integrative genomics methodologies, which aim to link properties of genes such as expression level, connectivity in biological networks, and sequence conservation to their function 76,77 to gain a broader understanding of their potential function.…”
Section: Prospects and Future Directionsmentioning
confidence: 99%
“…Even for the relatively small bacterial genomes, the function of many accessory genes remains unknown, with variable sequences derived from mobile genetic elements making inference about the role of the accessory genome challenging [11,13,15]. Previously methodologies have been developed, aiming to link properties of genes such as expression level, connectivity in biological networks, and sequence conservation to their function [79,81,95]. Similar approaches could be adopted to understand which accessory genes are likely to be functional and have phenotypic effects.…”
Section: Glossarymentioning
confidence: 99%
“…Early on gene expression evidence was mostly derived from expressed sequence tags (ESTs) and extended by full-length sequencing via cloning followed by Sanger sequencing. Later, the information was supplemented by RNASeq data from diverse tissues, and it was shown that gene models and isoforms with highly tissue-specific expression were underrepresented in exiting annotations (Cheng et al, 2017;Golicz et al, 2018b;Van Bel et al, 2019). Currently, addition of long reads generated by PacBio or Oxford Nanopore sequencing technologies allows for recovery of full-length transcripts, providing new insights into the extent of alternative splicing and transcriptome diversity (Cook et al, 2019).…”
Section: Accurate Gene Prediction and Functional Annotation For Precimentioning
confidence: 99%
“…For example, specialized databases integrating genotypic, phenotypic, and association data have been developed for rice (SNP-Seek), soybean (SoyBase), and wheat (T3; Grant et al, 2010;Blake et al, 2016;Mansueto et al, 2017). Beyond specialized database, tools like KnetMiner and MCRiceRepGP were developed aiming to rank candidate genes involved in biological processes of interest using multicriteria decision analysis (Hassani-Pak and Rawlings, 2017;Golicz et al, 2018b).…”
Section: Accurate Gene Prediction and Functional Annotation For Precimentioning
confidence: 99%
See 1 more Smart Citation